Dielectric properties and microstructure of SrTiO3/BaTiO3 multilayer thin films prepared by a chemical route - Pontes, F. M.; Leite, E. R.; Lee, EJH; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2001)
Multilayer thin films with perovskite structures were produced by the polymeric precursor method. SrTiO3/BaTiO3 (STO/BTO) multilayers were deposited on Pt(111)/Ti/SiO2/Si(100) substrates by the spin-coating technique and heated in air at 700 degreesC. The microstructure and crystalline phase of the multilayered thin films were examined by field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), resolution-high transmission electron microscopy (HRTEM), atomic force microscopy (AFM) and X-ray diffraction. The SrTiO3/BaTiO3 multilayer thin films consisted of grainy structures with an approximate grain size of 60 nm. The multilayered thin films showed a very clear interface between the components. The SrTiO3/BaTiO3 multilayer thin films revealed dielectric constants of approximately 527 and loss tangents of 0.03 at 100 kHz. The dielectric constant calculated for this multilayer film system is the value of the sum of each individual component of the film, i.e. The total value of the sum of each SrTiO3 (STO) and BaTiO3 (BTO) layer. The multilayer SrTiO3/BaTiO3 obtained by the polymeric precursor method, also showed a ferroelectric behavior with a remanent polarization of 2.5 muC/cm(2) and a coercive field of 30 kV/cm. The multilayer films displayed good fatigue characteristics under bipolar stressing after application of 10(10) switching cycles. (C) 2001 Published by Elsevier B.V. B.V. All rights reserved.
Keywords: multilayer thin films; dielectric constant; ferroelectric behavior; microstucture